Optimal light intensity for the growth of Rhodopseudomonas palustris strain B1 for application in sago and palm oil mill effluents treatment - Chong, L.L.; Ibrahim, S.; Vikineswary, S. (IWA Publishing, 2004)
The light intensity for the growth of the phototrophic R. plaustris strain B1 in glutamate-malate medium has been optimized at 4 klux. This condition was used for the treatment of sago effluent and POME using R. palustris strain B1, with three days retention time. At 10% (v/v) inoculum size, there was a 67% reduction for both COD and BOD of the sago effluent. By comparison the reductions in POME were only about 35% in undiluted effluent and 45% in 50% (v/v in tap water) diluted effluent.